CLEAVING MODELING OF CONCRETE IN THE ZONE ANCHORING FREE OF TENSION FITTING - Yu. V. Krasnoshchekov (Вестник СибАДИ, 2017)
The article presents the results of computer simulation of prototypes designed to test pull-out reinforcement of concrete. Analyzes the state of stress of concrete in the anchorage zone and identifies areas likely splitting the formation of cracks in elastic deformations of the materials. The calculation results are compared with experimental data. For a theoretical justification of a possible splintering involved elasticity problem of the action of a concentrated force at the point of infinite-finite body and a half.